THE HUMAN RESTLESSNESS AS A FOUNDING PRINCIPLE OF HOMO VIATOR IN ST. AUGUSTINE (Isagoge - Journal of Humanities and Social Sciences, 2022)
The human restlessness is one of the most fundamental themes of Augustinian anthropology. The man’s life is a tension to infinity that makes him live uneasily because he is dissatisfied with himself and, as a result, is immersed in a search for principles to supply that feeling of unrest in his soul, being called back move within to find your last ending. The research centralizes the studies on Augustine based on his analysis of human restlessness, having as its north the anthropological concept of homo viator. The homo viator is the being whose restlessness define his way of being, which is why he leads him to seek answers to innumerable doubts and questions about his existence.
Keywords: Homo viator; Happiness; God; Augustine; Restlessness